BEYOND REPRESENTATION: THE REVOLUTION AS WORD, AS IMAGE, AS EVENT - OUSMANOVA, ALMIRA (Politologija, 2013)
The “revolution” has been one of the key words in social and political thinking of the last two centuries. After the collapse of the Soviet Union and the closure of the era of political utopias (for many, the point of reference would be 1968 in Paris or in Prague), the word seemed to have vanished entirely from the current vocabulary. However, nowadays we are witnessing the return of the idea of Revolution to the political scene, to the media discourse, to social theory and to art. During the last few years, protest movements have became global and turned to be the real “festivals of resistance”, and this has been perceived as a symptom of the new “revolutionary situation”. The attempts of theoreticians (mostly of the post-Marxist thought) to critically revise the past experience vis-à-vis new political realities seem to be seriously retarded in comparison with the “revolutionary practice”. Passing over to the political scenarios for the future development of the situation, I will focus on the convergence of theoretical discourses on revolution, the new forms of political actionism (“Occupy!” movement, flash-mobs, silent protests, etc.) and the contemporary aesthetic praxis. The history of modern art and cinema has provided a rich iconography of the Revolution as an Event (from Delacrois to Eisenstein and further); however, contemporary art (public art first of all), together with political actionism, tends to follow an entirely different strategy which consists in the circumspect resistance to the logic of representation and is based on the concept of revolution as a perpetual nomadic movement, “becoming”, and evasion.